Malignant Alveolar Neoplasm in a 10-Month-Old French Bulldog - Ferreira, Manoel Luiz; Oliveira Neto, Plínio de Araújo; Rousso Filho, Raul; de Carvalho, Bruna Guedes; Silva, Paulo César; da Costa, Valéria Duarte Reis; Alves da Silva, Marcus Vinícius; Filho, Fernando Alzamora (Acta Scientiae Veterinariae, 2022)
Background: Malignant tumors are the main cause of death or euthanasia in animals. The oral cavity ranking fourth in number of occurrences. Epidemiological studies with dogs suggest that canine cancer kills 40-50% of individuals aged over 10 years. In view of the interest of academics and professionals in the healthcare of dogs and cats, this paper reports the case of a 10-month-old bitch, which, despite being a young animal, was affected alveolar rhabdomyosarcoma of abrupt evolution. Case: A 10-month-old French Bulldog bitch, weighing 10 kg, was referred to a veterinary hospital in the city of Rio de Janeiro for care. It had a history of mouth bleeding, after chewing a solid mineral material, edema in the region of the right maxilla, and protusion of the gland of the third eyelid. As the clinical examination also revealed a fracture of the maxillary canine, anti-inflammatory and antibiotics were prescribed, to be administered by the owner once a day for 7 days. During the next clinical examination, carried out one week later, an edema was found in the right region of the mouth, which proved difficult to examine. As the patient had already eaten, an appointment was made for the following day for an intervention int he operating room, where the animal could be anesthetized for better observation of the effected region. Blood was collected for hemogram, urea, creatinine, alkaline phosphatase, ALT, and GGT, and an 8 h food fasting and a 4 h water fasting were recommended. On that date, once the dog had been taken to the operating room, was administered the pre anesthesia, in addition to anesthetic induction and manutention. Upon examining the oral cavity, several loose molars were found on the right side, in addition to a tumoral aspect of the gum; thus, it was decided to collect a small sample of the tumoral mass for histopathology. The surgical specimen was placed in a formalin solution and sent to the laboratory for histopathological processing and diagnosis. One week later, the tumor mass was larger and the edema in the right region of the mouth was much larger than on the day of the procedure. Thus, a computerized tomography was requested to further investigate the alterations that had occurred in such a short time. Due to the results of the histopathology and the CT, an immunohistochemical test was suggested which determined the cell profile and morphology and confirmed the diagnosis of alveolar rhabdomyosarcoma according to clinical suspicion. The animal remained in the veterinary hospital for a further 48 h, during which the clinical condition worsened, with the animal suffering heavy bleeding. As the patient was no longer capable of oral intake of food or water, the decision was made with the consent of the owners to induce a painless death to alleviate the suffering of the animal. However, the owners did not authorize a necropsy. Discussion: Veterinary physicians should be conscious of the treatment of serious illnesses that will not result in a benefit for the patient. They should know when to stop the treatment to not cause further pain and suffering to the animals and their owners. Many of the interventions which aim to treat severe malignant neoplasia will not promote an improvement in quality of life or significantly extend the patient’s survival, and do not justify the suffering they entail. A painless death remains the best alternative in such cases. Keywords: cancer, malignant neoplasm, alveolar rhabdomyosarcoma, oral cavity.